The impact of advertising controllable elements on consumers' attitude towards the advertisement, brand and purchase intention - Arshad, Suhaila (Marketing, 2021)
Downstream fuel retailing among the major players in South Africa is highly competitive, and further compounded by the emergence of new players and changing customer orientation under the current price regulation environment. Marketing of fuel by way of expanding geographical coverage and the distribution network is no longer sustainable. Advertising benefits fuel companies by communicating their value proposition for brand differentiation, swaying consumer perception of fuel as a low involvement commodity with no difference in quality, and ultimately influencing their attitudes and behaviour. Fuel companies can take advantage of the advertising elements that have direct bearing – and are within their control – to make impactful advertisements to attract customers. Thus, this study investigates the influence of advertising controllable elements – namely, source and message – on attitude towards the advertisement, as well as attitude towards the brand and subsequently on purchase intention. A sample of 201 respondents was selected using convenience sampling method. The data was collected using an online self-administered questionnaire. Data analysis was performed using the Statistical Package for Social Sciences (SPSS) version 26.0. The relationship between the independent and the dependent variables was then examined using Structural Equation Modelling (SEM) with Analysis of Moment Structures (AMOS) version 26.0. The study findings established that attitude towards the advertisement is positively and significantly influenced by source credibility, source likeability and emotional message. Rational message has a positive impact on attitude towards the advertisement, albeit insignificant. Meanwhile, only source credibility and rational message have positive significant effects on attitude towards the brand. The impact of source likeability on brand attitude although positive, is not significant. Contrariwise, emotional message has neither influence nor significant effect on attitude towards the brand. Moreover, the study findings showed that while attitude towards the advertisement positively influences brand attitude, it does not influence purchase intention. The purchase intention for fuel is nonetheless influenced by attitude towards the brand. This study offers useful insights that can be used to create an impactful fuel advertisement, leveraging on source attributes and message appeals to influence consumers' attitudinal as well as behavioural intention.